Minnow Trap Color Effectiveness Test Using Cat Food Bait as Aquatic Sampling Gear on Diurnal Fish in Gajah Mungkur Reservoir, Cental Java, Indonesia - Arifianto, Adityas; Mufti, Elsa; Marhendra, Agung Pramana Warih; Kurniawan, Nia (The Journal of Experimental Life Science, 2021)
The Minnow Trap is a simple sampling gear, efficient, easy to operate, affordable, easy to make, and has been used in research in the fisheries and aquatic ecology for more than 90 years. The brightness, color, and visual obstruction of fishing gear or fish traps affect the behavioral response of target fish, considering that each fish has a specific level of color sensitivity. The color effectiveness test of fishing gear is an important prerequisite for the use of sampling tools, and it needs to be evaluated to understand the gear performance and avoid potential sampling bias. The purpose of this study was to test the color effect of the minnow trap on diurnal fish in the Gajah Mungkur Reservoir waters. The research was carried out in Gajah Mungkur Reservoir, Wonogiri Regency, at two stations. The sampling conducted at 09.00 - 11.00 and 13.00 - 15.00 Indonesian West Time, where the initial survey is estimated to be the highest time for diurnal fish activity. The minnow trap used in this study is four colors vinyl-painted double funnel cylindrical minnow trap with a 5x5 millimeter mesh size and a conventional umbrella minnow trap used as control. The sampling results are then recorded on the datasheet and analyzed using Microsoft Excel. CPUE (Catch Per Effort Unit) of each unit is then calculated and statistically analyzed by Kruskal-Wallis test and Kolmogorov-Smirnov normality test through SPSS 25.0 software. The test result of five unit minnow traps from 40 installations and two hours of deployment time, 80 individuals were captured, consisted of seven species of freshwater fish. CPUE values ranking consecutively from the highest from silver units (1.375), black (1.25), green (1.125), red (0.9375), and control (0.3125). The Kruskal-Wallis analysis showed that all tested units do not have a significant difference. Keywords: Color, catch per unit effort, fish, minnow trap.